Comparison of Envelope and Modified Triangular Flaps on Incidence of Dry Socket after Surgical Removal of Impacted Mandibular Third Molars - Umair, Hanzla; Farooq, Muhammad Umar; Muhammad Afzal; Baluch, Rahila Aziz (Indus Journal of Bioscience Research, 2025)
Objectives: To compare the incidence of dry socket between envelope and modified triangular flaps in patients undergoing surgical removal of impacted mandibular third molars. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Oral and Maxillofacial Surgery, 30 Military Dental Centre, Combined Military Hospital Peshawar, and Pakistan Institute of Medical Sciences, Islamabad, from December 2022 to November 2024. Methods: A total of 94 patients aged 18-50 years undergoing surgical extraction of impacted mandibular third molars were included and allocated to two equal groups.  Patients in Group EF received an envelope flap created by an intersulcular incision from the first to second molar, extending onto the ramus and laterally diverging distal to the third molar in order to protect the lingual nerve. In Group MTF; a modified triangular flap was created with an incision from the ramus ridge to 2 mm distal to the second molar, then extended into the buccal vestibule while preserving a thin gingival collar around the second molar. Patients were evaluated on postoperative day 3 for the development of dry socket, diagnosed by the presence of exposed alveolar bone and pain score> 7 on visual analogue scale. Chi-square test applied to compare the primary outcomes between the two groups. Results: The mean age of participants was 30.6±6.5 years, with a higher male population (66%). No statistically significant difference was reported between the Group EF and Group MTF regarding the incidence of dry socket (19.2% Vs 17%, p-value= 0.79). Conclusion: Both envelope and modified triangular flap methods demonstrate a comparable efficacy in preventing dry socket after mandibular third molar surgery.